1988
DOI: 10.1113/jphysiol.1988.sp017413
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus nuclear magnetic resonance studies on the effect of duration of contraction in bull‐frog skeletal muscles.

Abstract: SUMMARY1. Contraction and recovery of bull-frog skeletal muscles were studied using 31p nuclear magnetic resonance (NMR), with a time resolution of 16 s, at 4 'C. The muscles were stimulated tetanically for various periods (0-2-10 s) at a sarcomere length of 2 4 ,um. Changes in the concentrations of inorganic phosphate (Pi), phosphocreatine (PCr) and other metabolites were studied for repeated cycles of contraction and recovery.2. In resting muscles, bathed in a solution gassed with 95% 02 and 5% C02, the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…During a fatiguing series of tetani, inorganic phosphate probably does accumulate because the time constant for its removal by oxidative phosphorylation (Kawano, Tanokura & Yamada, 1988) is much longer than the 10 s intervals between tetani used here. It is well established from experiments on skinned fibres that an increase in Pi level depresses both force and myofibrillar ATPase and that the effect on ATPase is less than that on force (Bowater & Sleep, 1988).…”
Section: Interpretation Of Changes In Non-crossbridge Heatmentioning
confidence: 98%
“…During a fatiguing series of tetani, inorganic phosphate probably does accumulate because the time constant for its removal by oxidative phosphorylation (Kawano, Tanokura & Yamada, 1988) is much longer than the 10 s intervals between tetani used here. It is well established from experiments on skinned fibres that an increase in Pi level depresses both force and myofibrillar ATPase and that the effect on ATPase is less than that on force (Bowater & Sleep, 1988).…”
Section: Interpretation Of Changes In Non-crossbridge Heatmentioning
confidence: 98%
“…It is very likely that Pi concentration increases in moderate fatigue studied here; Kawano, Tanokura & Yamada (1988) have measured the time constant for recovery of P1 to its initial value to be approximately 30 min after a tetanus of frog muscle at 4 'C. The time constant was independent of tetanus duration in the range tested, 0 2-10 s. Pi recovery would therefore not be complete under the moderate fatigue conditions used here, so Pi concentration would increase.…”
Section: Acidification Pi and Fatiguementioning
confidence: 99%
“…The methods are similar to those described previously (in more detail) by Kawano et al (1988). A muscle chamber (muscle holder and 20 mm NMR sample tube) was used in which eight pairs of soleus muscles were mounted.…”
Section: Nmr Measurementsmentioning
confidence: 99%
“…Studies in toad and frog muscle have already revealed post-contractile PCr splitting at certain temperatures (Yamada & Tanokura, 1983; Kawano, Tanokura & Yamada, 1988).…”
Section: Introductionmentioning
confidence: 99%